Making their way as academics: A qualitative study examining how nurse academics understand and (re)construct academic identity. (May 2021) - Barrow, Mark; Xu, Linlin
Abstract: Objectives: This study aims to explore the way in which nurse academics understand and (re)construct their academic identity. Design: An exploratory qualitative approach was adopted. Methods: Individual semi-structured interviews were conducted with 15 nurse academics who were employed in positions requiring both research and teaching in two New Zealand university nursing schools. Participants' demographic information and critical career incidents were also collected. Interview data were analysed thematically. Results: Nurse academics understand their academic identity as research-related, relational and dynamic. Although their academic identity can be in conflict with their clinical one, the former is (re)constructed as an extension of the latter. To navigate each university's multiple expectations of academics, nurse academics in this study strive to maintain their engagement with teaching, research and clinical practice, although in some cases, clinical practice is reconceptualised in relation to teaching and researching rather than direct contact with patients. Conclusion: Academic identity development is fluid and interdependent on that of clinical identity in this young and vocationally-based discipline. There is an interrelated, dual process of identity (re)construction – while (re)constructing academic identity, nurse academics also reshape and redefine their clinical identity. The trajectory of their identity development challenges institutions to consider the needs of nurse academics (and others in similar disciplines) by recognising and supporting the maintenance of a form of clinical currency in order to strengthen the discipline within the academy.